Science and technology breakthroughs from the wheel to the World Wide Web - Bruno, Leonard C. (U.X.L., 1998)
Highlights milestones in agriculture, astronomy, biology, chemistry, communications, computers, earth sciences, energy, mathematics, medicine, physics, and transportation from prehistory to the present.